Bone cement for orthopedic repair and preparation method thereof
By using a Schiff base dynamic network of composite calcium phosphate salt and modified toughening agent, and polydopamine-gallic acid grafting of antibacterial agent, the problems of insufficient toughness and antibacterial properties of calcium phosphate bone cement are solved, achieving bone cement effects with high toughness, self-healing and strong antibacterial properties.
Patent Information
- Application Number
- CN202511349070.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-22
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-09-22
AI Technical Summary
Existing calcium phosphate bone cements are insufficient in terms of toughness and antibacterial properties, and have limited self-healing capabilities, resulting in implants that are fragile and have a high risk of infection.
A combination of composite calcium phosphate salt, bioactive glass, developer, modified toughening agent and antibacterial agent is used to improve toughness, self-healing properties and antibacterial properties through the dynamic network of Schiff base bonds in the modified toughening agent and the polydopamine-gallic acid grafting of the antibacterial agent.
It achieves high toughness, self-healing ability and strong antibacterial properties in bone cement, extending its service life and reducing the risk of infection.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of bone cement technology, specifically to a bone cement for orthopedic repair and its preparation method. Background Technology
[0002] Bone cement (such as polymethyl methacrylate (PMMA) bone cement and calcium phosphate (CMP) bone cement) is a commonly used filling and fixation material in orthopedic clinics, widely applied in fracture fixation, artificial joint replacement, and vertebroplasty. Among these, CMP bone cement, due to its inorganic composition similar to human bone tissue, biodegradability, and osteoconductivity, has become an ideal alternative to traditional PMMA bone cement (which is non-degradable and prone to exothermic damage). However, existing CMP bone cement still faces some technical challenges that limit its clinical application. CMP bone cement is mainly composed of calcium phosphate powder mixed with a liquid phase and then solidified. Its crystalline structure is dense but lacks toughness, making it prone to implant breakage due to the accumulation of microcracks, especially in weight-bearing bone repair where the failure rate is high. Traditional toughening methods (such as adding linear polymers or fibers) suffer from weak interfacial bonding and easy aggregation, making it difficult to balance strength and toughness. Furthermore, CMP bone cement's self-healing ability is also insufficient. In addition, bone cement implantation is prone to infection; existing antibiotic-loaded bone cements pose risks of "burst release" and "drug resistance," while silver ion-loaded materials may cause cytotoxicity.
[0003] Chinese invention patent CN120204462A discloses a high-flexibility injectable magnesium phosphate bone cement and its preparation method. This high-flexibility injectable magnesium phosphate bone cement comprises solid powder, reinforcing filler, and water. The solid powder comprises the following components by weight: 50-70 parts magnesium phosphate salt and 30-50 parts hydrogen phosphate salt, wherein the magnesium phosphate salt includes trimagnesium phosphate. The reinforcing filler comprises a polyurethane-modified epoxy resin emulsion. Based on a solid content of 30%-50% in the polyurethane-modified epoxy resin emulsion, the mass fractions of solid powder, reinforcing filler, and water in the bone cement are 66-70 wt%, 1-7 wt%, and 23-33 wt%, respectively. This high-flexibility injectable magnesium phosphate bone cement exhibits high flexural strength and is suitable for bone defect areas subjected to multi-directional loads, but it has poor antibacterial properties and lacks self-healing ability. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the purpose of this invention is to provide a bone cement for orthopedic repair and its preparation method.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A bone cement for orthopedic repair includes a solid powder and a liquid component; The solid powder comprises the following components in parts by weight: 55-65 parts of composite calcium phosphate, 10-15 parts of bioactive glass, 2-3 parts of developer, 1-2 parts of hydroxyapatite, 8-12 parts of modified toughening agent, and 2-3 parts of nanocellulose fiber. The liquid phase component comprises the following components in parts by weight: 40-50 parts sodium alginate solution, 10-20 parts methacrylamide gelatin, 0.5-1 part transglutaminase, 30-60 parts citrate buffer, and 1-2 parts antibacterial agent.
[0006] The modified toughening agent is prepared by the following method: S1: Under nitrogen protection, pentaerythritol, 12-oxododecanoic acid and anhydrous toluene were mixed, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 4-dimethylaminopyridine were added. The mixture was reacted at 80-100℃ for 6-8 h to obtain intermediate 1. S2: Under nitrogen protection, intermediate 1, dopamine and anhydrous ethanol are mixed, triethylamine and ascorbic acid are added, and the mixture is reacted at 30-40℃ for 5-7 hours to obtain the modified toughening agent.
[0007] In step S1, the molar ratio of pentaerythritol to 12-oxododecanoic acid is 1:(4.1-4.3).
[0008] In step S2, the molar ratio of intermediate 1 to dopamine is 1:(4.05-4.2).
[0009] The antibacterial agent is prepared by the following method: N1: Under nitrogen protection, polydopamine and anhydrous DMF were mixed evenly, triethylamine was added and mixed evenly, and then 4-aminosulfonylbenzoyl chloride was added. The mixture was reacted at 30-40℃ for 5-7 hours to obtain intermediate A. N2: Under nitrogen protection, gallic acid and anhydrous DMF are mixed, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are added for activation; then the mixture is slowly added to the PBS buffer of intermediate A and reacted at 25-30℃ for 7-9 hours to obtain the antibacterial agent.
[0010] In step N1, the mass ratio of polydopamine to 4-aminosulfonylbenzoyl chloride is 1:(0.46-0.51).
[0011] In step N2, the mass ratio of intermediate A to gallic acid is 1:(0.25-0.27).
[0012] The composite calcium phosphate salt includes α-tricalcium phosphate and β-tricalcium phosphate, wherein α-tricalcium phosphate accounts for 70% by weight and β-tricalcium phosphate accounts for 30% by weight; the developer is tantalum powder; and the nanocellulose fiber is bacterial cellulose.
[0013] The sodium alginate solution has a concentration of 2 wt%; the citrate buffer solution has a concentration of 0.1 M and a pH of 6.5.
[0014] A method for preparing bone cement for orthopedic repair includes the following steps: (1) Weigh out the following by weight: 55-65 parts of compound calcium phosphate, 10-15 parts of bioactive glass, 2-3 parts of developer, 1-2 parts of hydroxyapatite, 8-12 parts of modified toughening agent, 2-3 parts of nanocellulose fiber, 40-50 parts of sodium alginate solution, 10-20 parts of methacrylamide gelatin, 0.5-1 part of transglutaminase, 30-60 parts of citrate buffer, and 1-2 parts of antibacterial agent; (2) First, freeze-dry the nanocellulose fibers to obtain dried nanocellulose fibers. Then, mix the composite calcium phosphate salt, bioactive glass, developer, hydroxyapatite, dried nanocellulose fibers and modified toughening agent in a three-dimensional mixer to obtain solid powder. (3) Mix methacrylamide gelatin with citrate buffer, stir and mix in a water bath at 60°C, and cool to room temperature in the dark; add transglutaminase and antibacterial agent to sodium alginate solution, and sonicate at 300W for 5 min; mix the two solutions in the dark and stir to obtain the liquid phase component; (4) Mix the solid powder and liquid components at a mass ratio of 3:1 and stir to obtain bone cement for orthopedic repair.
[0015] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include: (1) The modified toughening agent prepared in this invention constructs a four-arm Schiff base dynamic network through aldehyde-amino condensation, which can simultaneously impart mechanical properties, self-healing properties, interfacial bonding strength and fatigue resistance to bone cement. When microcracks occur in bone cement, the Schiff base bonds are triggered by hydrolytic fracture through the infiltration of body fluids, and then recombine to form new Schiff base bonds at physiological pH, which can realize the "damage-repair" cycle; the hydroxyl groups on the surface of the modified toughening agent can form coordination bonds with calcium ions on the surface of calcium phosphate and form hydrogen bonds with hydroxyapatite, thereby improving the interfacial bonding strength; the dynamic Schiff base bonds can dissipate energy through "fracture-reorganization" under cyclic loading, thus extending the service life of bone cement in vivo.
[0016] (2) The antibacterial agent prepared in this invention has gallic acid grafted onto the surface of polydopamine. The phenolic hydroxyl groups of gallic acid can destroy the bacterial cell membrane, inhibit biofilm formation, and improve antibacterial performance. Polydopamine itself has excellent biocompatibility and antioxidant properties. The synergistic effect of polydopamine grafted with gallic acid can greatly improve the antibacterial performance of bone cement. Detailed Implementation
[0017] The following description, in conjunction with specific embodiments, provides further details, but the present invention is not limited to these embodiments.
[0018] Example 1: Preparation of modified toughening agent: S1: Under nitrogen protection, 0.1 mol pentaerythritol and 0.41 mol 12-oxododecanoic acid were added to 800 mL of anhydrous toluene and stirred until homogeneous. Then, 0.4 mol 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.1 mol 4-dimethylaminopyridine were added. The mixture was reacted at 80 °C for 8 h, filtered, and rotary evaporated at 60 °C for 3 h. The mixture was then subjected to silica gel column chromatography (eluent: petroleum ether / ethyl acetate). V / V The mixture of 5:1 (ratio) was purified and rotary evaporated at 50°C for 3 hours to obtain intermediate 1; the reaction equation is shown below:
[0019] Its 1H NMR data are as follows: 1 H NMR (500 MHz, Chloroform- d ) δ 9.57 (s, 4H), 4.31-4.16 (m, 8H), 2.51 (s, 8H), 2.30 (s, 8H), 1.59 (d, J = 2.4 Hz, 16H), 1.37-1.24 (m, 48H).
[0020] S2: Under nitrogen protection, 0.1 mol of intermediate 1 and 0.405 mol of dopamine were added to 900 ml of anhydrous ethanol and stirred until homogeneous. Then, 0.1 mol of triethylamine and 0.05 mol of ascorbic acid were added, and the mixture was reacted at 30°C in the dark for 7 h. The pH was adjusted to 5 with 1 M hydrochloric acid, and the mixture was rotary evaporated at 40°C for 5 h. The residue was dissolved in 1000 ml of anhydrous ethanol / water (anhydrous ethanol to water volume ratio of 1:14), dialyzed with deionized water containing 0.1 wt% ascorbic acid (molecular weight cutoff 1000 Da) for 72 h (changing the solution every 6 hours, 2000 ml each time), and freeze-dried at -50°C for 24 h to obtain the modified toughening agent. The reaction equation is shown below:
[0021] Its 1H NMR data are as follows: 1 H NMR (500 MHz, Chloroform- d) δ 7.39 (d, J = 86.1 Hz, 4H), 6.71-6.64(m, 12H), 6.19 (d, J = 50.6 Hz, 8H), 4.32-4.15 (m, 8H), 3.79 (s, 8H), 2.84(d, J = 0.9 Hz, 8H), 2.30 (s, 8H), 2.10 (s, 8H), 1.59 (s, 8H), 1.57 (s, 8H), 1.35-1.26 (m, 48H).
[0022] Example 2: Preparation of modified toughening agent: S1: Under nitrogen protection, 0.1 mol pentaerythritol and 0.42 mol 12-oxododecanoic acid were added to 800 mL of anhydrous toluene and stirred until homogeneous. Then, 0.4 mol 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.1 mol 4-dimethylaminopyridine were added. The mixture was reacted at 85 °C for 7 h, filtered, and rotary evaporated at 60 °C for 3 h. The mixture was then subjected to silica gel column chromatography (eluent: petroleum ether / ethyl acetate). V / V Purify the mixture by a ratio of 5:1, and rotary evaporate at 50°C for 3 hours to obtain intermediate 1; S2: Under nitrogen protection, 0.1 mol of intermediate 1 and 0.41 mol of dopamine were added to 900 ml of anhydrous ethanol and stirred until homogeneous. Then, 0.1 mol of triethylamine and 0.05 mol of ascorbic acid were added, and the mixture was reacted at 35°C in the dark for 6 h. 1 M hydrochloric acid was added to adjust the pH to 5, and the mixture was rotary evaporated at 40°C for 5 h. The residue was dissolved in 1000 ml of anhydrous ethanol / water (anhydrous ethanol to water volume ratio of 1:14), dialyzed with deionized water containing 0.1 wt% ascorbic acid (molecular weight cutoff 1000 Da) for 72 h (the solution was changed every 6 hours, 2000 ml each time), and freeze-dried at -50°C for 24 h to obtain the modified toughening agent.
[0023] Example 3: Preparation of modified toughening agent: S1: Under nitrogen protection, 0.1 mol pentaerythritol and 0.43 mol 12-oxododecanoic acid were added to 800 mL of anhydrous toluene and stirred until homogeneous. Then, 0.4 mol 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.1 mol 4-dimethylaminopyridine were added. The mixture was reacted at 90 °C for 6 h, filtered, and rotary evaporated at 60 °C for 3 h. The mixture was then subjected to silica gel column chromatography (eluent: petroleum ether / ethyl acetate). V / V Purify the mixture by a ratio of 5:1, and rotary evaporate at 50°C for 3 hours to obtain intermediate 1; S2: Under nitrogen protection, 0.1 mol of intermediate 1 and 0.42 mol of dopamine were added to 900 ml of anhydrous ethanol and stirred until homogeneous. Then, 0.1 mol of triethylamine and 0.05 mol of ascorbic acid were added, and the mixture was reacted at 40°C in the dark for 5 h. 1 M hydrochloric acid was added to adjust the pH to 5, and the mixture was rotary evaporated at 40°C for 5 h. The residue was dissolved in 1000 ml of anhydrous ethanol / water (anhydrous ethanol to water volume ratio of 1:14), dialyzed with deionized water containing 0.1 wt% ascorbic acid (molecular weight cutoff 1000 Da) for 72 h (the solution was changed every 6 hours, 2000 ml each time), and freeze-dried at -50°C for 24 h to obtain the modified toughening agent.
[0024] Example 4: Preparation of antibacterial agent: N1: Under nitrogen protection, 10g of polydopamine was mixed with 150ml of anhydrous DMF, 2.1g of triethylamine was added, and the mixture was stirred until homogeneous. Then, 4.6g of 4-aminosulfonylbenzoyl chloride was added (in four equal batches, 10min apart), and the mixture was reacted at 30℃ in the dark for 7h. 500ml of deionized water was added and the mixture was stirred to precipitate. The precipitate was centrifuged at 8000rpm for 10min, washed three times with 50ml of anhydrous ethanol each time, and dried under vacuum at 40℃ for 8h to obtain intermediate A. The reaction equation is shown below:
[0025] N2: Under nitrogen protection and in an ice bath, 300 ml of anhydrous DMF and 25 g of gallic acid were mixed thoroughly. 35 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 21 g of N-hydroxysuccinimide were weighed, mixed, and then added in 5 equal batches (5 min apart) to the gallic acid DMF solution. The mixture was stirred and activated in an ice bath for 45 min. At room temperature, 100 g of intermediate A was added to 500 ml of anhydrous DMF and sonicated for 10 min under nitrogen protection. Then, 200 ml of PBS buffer (0.1 M, pH 7.4) was added and mixed thoroughly. The activated gallic acid DMF solution was slowly added dropwise under light-protected conditions. After 1 hour of dropwise addition, the reaction was carried out at 25°C in the dark for 9 hours (using 0.1 M PBS buffer during the reaction). The pH of the solution was maintained between 7.2 and 7.6 using an HCl / NaOH solution. After the reaction, the mixture was placed in a dialysis bag with a molecular weight cutoff of 8000 Da and dialyzed with deionized water for 72 hours (changing the water every 6 hours, 2000 ml each time). The mixture was then freeze-dried at -50°C for 24 hours to obtain the antibacterial agent. The reaction equation is shown below.
[0026] Example 5: Preparation of antibacterial agent: N1: Under nitrogen protection, 10g of polydopamine was mixed with 150ml of anhydrous DMF, 2.2g of triethylamine was added, and the mixture was stirred until homogeneous. Then, 4.9g of 4-aminosulfonylbenzoyl chloride was added (in four equal batches, with a 10min interval between each batch), and the mixture was reacted at 35℃ in the dark for 6h. 500ml of deionized water was added and stirred to precipitate the product. The product was centrifuged at 8000rpm for 10min, washed three times with anhydrous ethanol (50ml each time), and dried under vacuum at 40℃ for 8h to obtain intermediate A. N2: Under nitrogen protection and in an ice bath, mix 300ml of anhydrous DMF and 26g of gallic acid thoroughly. Weigh 35g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 21g of N-hydroxysuccinimide, mix them, and then add them in 5 equal batches (5 min apart) to a gallic acid DMF solution. Activate the mixture by stirring in an ice bath for 45 min. At room temperature, add 100g of intermediate A to 500ml of anhydrous DMF and sonicate under nitrogen protection for 10 min. Then add 200ml of PBS buffer (0.1M, pH 7.4), stir to mix thoroughly, and slowly add the activated gallic acid DMF solution dropwise under light-protected conditions. After 1 hour of dropwise addition, react at 25℃ in the dark for 8 hours (using 0.1M...) The pH of the solution was maintained between 7.2 and 7.6 using HCl / NaOH solution. After the reaction was completed, the mixture was placed into a dialysis bag with a molecular weight cutoff of 8000 Da and dialyzed with deionized water for 72 hours (changing the water every 6 hours, 2000 ml each time). The mixture was then freeze-dried at -50℃ for 24 hours to obtain the antibacterial agent.
[0027] Example 6 Preparation of antibacterial agent: N1: Under nitrogen protection, 10g of polydopamine was mixed with 150ml of anhydrous DMF, 2.3g of triethylamine was added, and the mixture was stirred until homogeneous. Then, 5.1g of 4-aminosulfonylbenzoyl chloride was added (in four equal batches, with a 10min interval between each batch), and the mixture was reacted at 35℃ in the dark for 5h. 500ml of deionized water was added and stirred to precipitate the product. The product was centrifuged at 8000rpm for 10min, washed three times with anhydrous ethanol (50ml each time), and dried under vacuum at 40℃ for 8h to obtain intermediate A. N2: Under nitrogen protection and in an ice bath, 300 ml of anhydrous DMF and 27 g of gallic acid were stirred and mixed thoroughly. 35 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 21 g of N-hydroxysuccinimide were weighed, mixed, and then added in 5 equal batches (5 min apart) to the gallic acid DMF solution. The mixture was stirred and activated in an ice bath for 45 min. At room temperature, 100 g of intermediate A was added to 500 ml of anhydrous DMF and ultrasonically dispersed for 10 min under nitrogen protection. Then, 200 ml of PBS buffer (0.1 M, pH 7.4) was added and stirred thoroughly. The activated gallic acid DMF solution was slowly added dropwise under light-protected conditions. After 1 hour of dropwise addition, the mixture was reacted at 30°C in the dark for 7 hours (using 0.1 M PBS buffer during the reaction). The pH of the solution was maintained between 7.2 and 7.6 using HCl / NaOH solution. After the reaction was completed, the mixture was placed into a dialysis bag with a molecular weight cutoff of 8000 Da and dialyzed with deionized water for 72 hours (changing the water every 6 hours, 2000 ml each time). The mixture was then freeze-dried at -50℃ for 24 hours to obtain the antibacterial agent.
[0028] Example 7: Preparation of bone cement for orthopedic repair: (1) Weigh the following by weight: 55g of compound calcium phosphate (38.5g of α-tricalcium phosphate and 16.5g of β-tricalcium phosphate), 10g of bioactive glass, 2g of developer (tantalum powder), 1g of hydroxyapatite, 8g of modified toughening agent (prepared in Example 1), 2g of nanocellulose fiber (bacterial cellulose), 40g of sodium alginate solution (2wt%), 10g of methacrylamide gelatin, 0.5g of transglutaminase, 30g of citrate buffer (0.1M, pH=6.5), and 1g of antibacterial agent (prepared in Example 4); (2) First, put the nanocellulose fibers into a freeze dryer and freeze dry at -50℃ for 12h to obtain dried nanocellulose fibers. Then, the composite calcium phosphate salt, bioactive glass, developer, hydroxyapatite, dried nanocellulose fibers and modified toughening agent are mixed in a three-dimensional mixer at 60rpm for 2h to obtain solid powder. (3) Mix methacrylamide gelatin with citrate buffer (0.1M, pH=6.5), stir and mix in a 60℃ water bath, and cool to room temperature in the dark; add transglutaminase and antibacterial agent to 2wt% sodium alginate solution, and disperse by ultrasonication at 20kHz for 5min; under dark conditions, mix the two solutions and stir magnetically at 500rpm for 10min to obtain the liquid phase component; (4) Mix the solid powder and liquid components at a mass ratio of 3:1 and stir for 5 minutes to obtain bone cement for orthopedic repair.
[0029] Example 8: Preparation of bone cement for orthopedic repair: (1) Weigh the following by weight: 60g of compound calcium phosphate salt (42g of α-tricalcium phosphate and 18g of β-tricalcium phosphate), 13g of bioactive glass, 2.5g of developer (tantalum powder), 1.5g of hydroxyapatite, 10g of modified toughening agent (prepared in Example 2), 2.5g of nanocellulose fiber (bacterial cellulose), 45g of sodium alginate solution (2wt%), 15g of methacrylamide gelatin, 0.8g of transglutaminase, 45g of citrate buffer (0.1M, pH=6.5), and 1.5g of antibacterial agent (prepared in Example 5); (2) First, put the nanocellulose fibers into a freeze dryer and freeze dry at -50℃ for 12h to obtain dried nanocellulose fibers. Then, the composite calcium phosphate salt, bioactive glass, developer, hydroxyapatite, dried nanocellulose fibers and modified toughening agent are mixed in a three-dimensional mixer at 60rpm for 2h to obtain solid powder. (3) Mix methacrylamide gelatin with citrate buffer (0.1M, pH=6.5), stir and mix in a 60℃ water bath, and cool to room temperature in the dark; add transglutaminase and antibacterial agent to a 2wt% sodium alginate solution, and disperse by ultrasonication at 20kHz for 5min; under dark conditions, mix the two solutions and stir magnetically at 500rpm for 10min to obtain the liquid phase component; (4) Mix the solid powder and liquid components at a mass ratio of 3:1 and stir for 5 minutes to obtain bone cement for orthopedic repair.
[0030] Example 9: Preparation of bone cement for orthopedic repair: (1) Weigh the following by weight: 65g of compound calcium phosphate (45.5g of α-tricalcium phosphate and 19.5g of β-tricalcium phosphate), 15g of bioactive glass, 3g of developer (tantalum powder), 2g of hydroxyapatite, 12g of modified toughening agent (prepared in Example 3), 3g of nanocellulose fiber (bacterial cellulose), 50g of sodium alginate solution (2wt%), 20g of methacrylamide gelatin, 1g of transglutaminase, 60g of citrate buffer (0.1M, pH=6.5), and 2g of antibacterial agent (prepared in Example 6); (2) First, put the nanocellulose fibers into a freeze dryer and freeze dry at -50℃ for 12h to obtain dried nanocellulose fibers. Then, the composite calcium phosphate salt, bioactive glass, developer, hydroxyapatite, dried nanocellulose fibers and modified toughening agent are mixed in a three-dimensional mixer at 60rpm for 2h to obtain solid powder. (3) Mix methacrylamide gelatin with citrate buffer (0.1M pH=6.5), stir and mix in a 60℃ water bath, and cool to room temperature in the dark; add transglutaminase and antibacterial agent to a 2wt% sodium alginate solution, and disperse by ultrasonication at 20kHz for 5min; mix the two solutions in the dark, and stir magnetically at 500rpm for 10min to obtain the liquid phase component; (4) Mix the solid powder and liquid components at a mass ratio of 3:1 and stir for 5 minutes to obtain bone cement for orthopedic repair.
[0031] Comparative Example 1 The raw material composition and preparation method of bone cement for orthopedic repair are basically the same as those in Example 8, except that no modified toughening agent is added to the components.
[0032] Comparative Example 2 The raw material composition and preparation method of bone cement for orthopedic repair are basically the same as those in Example 8, except that no antibacterial agent is added to the components.
[0033] Comparative Example 3 The raw material composition and preparation method of the bone cement for orthopedic repair are basically the same as in Example 8, except that the modified toughening agent is replaced with an equal weight of the modified toughening agent prepared by the following method: The preparation method of the modified toughening agent is basically the same as that in Example 2, except that 12-oxododecanoic acid in step S1 is replaced with an equimolar amount of 5-oxopentanoic acid.
[0034] Comparative Example 4 The raw material composition and preparation method of the bone cement for orthopedic repair are basically the same as in Example 8, except that the modified toughening agent is replaced with an equal weight of the modified toughening agent prepared by the following method: The preparation method of the modified toughening agent is basically the same as that in Example 2, except that the dopamine in step S2 is replaced with an equimolar amount of p-hydroxyphenylethylamine.
[0035] Comparative Example 5 The raw material composition and preparation method of the bone cement for orthopedic repair are basically the same as in Example 8, except that the modified toughening agent is replaced with an equal weight of the modified toughening agent prepared by the following method: The preparation method of the modified toughening agent is basically the same as that in Example 2, except that the amount of dopamine added in step S2 is reduced to 0.2 mol.
[0036] Comparative Example 6 The raw material composition and preparation method of bone cement for orthopedic repair are basically the same as in Example 8, except that the antibacterial agent is replaced with an equal weight of antibacterial agent prepared by the following method: The preparation method of the antibacterial agent is basically the same as that in Example 5, except that the 4-aminosulfonylbenzoyl chloride in step N1 is replaced with an equal weight of 4-aminobenzoyl chloride.
[0037] Comparative Example 7 The raw material composition and preparation method of bone cement for orthopedic repair are basically the same as in Example 8, except that the antibacterial agent is replaced with an equal weight of antibacterial agent prepared by the following method: The preparation method of the antibacterial agent is basically the same as that in Example 5, except that gallic acid in step N2 is replaced with an equal weight of p-hydroxybenzoic acid.
[0038] The tantalum powder used in the embodiments and comparative examples of this application is medical grade ML-Ta-N50, produced by Zhejiang Manli Nanotechnology Co., Ltd.; the bacterial cellulose is bacterial cellulose dispersion TL-008, produced by Nanjing Tianlu Nanotechnology Co., Ltd.; the bioactive glass is medical grade HQ-BG45s-D1, produced by Kunshan Huaqiao Science and Technology New Materials Co., Ltd.; the hydroxyapatite is HAP03-20, produced by Nanjing Junzhuo Biotechnology Co., Ltd.; the methacryloyl gelatin is EFL-GM-60; the sodium alginate is medical grade with a viscosity of 600 mPa·s, produced by Qingdao Mingyue Marine New Materials Technology Co., Ltd.; the polydopamine has a number-average molecular weight of 1000 Da. The CAS number of 4-aminosulfonylbenzoyl chloride is 51594-97-9.
[0039] The compressive strength, flexural strength, and antibacterial properties of the bone cements prepared in Examples 7-9 and Comparative Examples 1-7 for orthopedic repair were tested. The test results are shown in Table 1.
[0040] The compressive and flexural strength of the bone cement were tested according to the YY 0459-2003 standard. A universal testing machine was used for compressive strength testing at a loading rate of 20 mm / min and for flexural strength testing at a loading rate of 5 mm / min. The samples were kept at 23℃ for 24 hours before testing.
[0041] Specimen preparation for bending test: 100g of bone cement prepared in the comparative example and the example were poured into a polytetrafluoroethylene mold, cured at 37°C for 1h, and demolded to obtain specimens (specimen dimensions: length 75 mm, width 10 mm, depth 3.3 mm). Preparation of test specimens for compressive strength test: 100g of bone cement prepared in the comparative example and the example were poured into a polytetrafluoroethylene cylindrical mold, cured at 37℃ for 1h, and demolded to obtain the specimen (the specimen size is 6mm in diameter and 12mm in length). Specimen damage repair test: A damage incision (0.5 mm deep and 10 mm long) was made at the center of the gauge length of the specimen with a blade, and then the specimen was immersed in 50 ml of PBS buffer at 37℃, 0.1 M, pH=7.4 for 24 h to obtain the repaired bone cement.
[0042] The antibacterial effect of bone cement was tested using an inhibition loop method. Staphylococcus aureus was selected as the target bacterial species. The lyophilized powder of the bacterial species was mixed with resuscitation solution and shaken to prepare a bacterial suspension for subculturing. This bacterial suspension was inoculated onto slant agar plates using an inoculation loop and cultured for 24 hours. Subsequently, it was inoculated onto plate agar plates and cultured for another 24 hours to obtain second-generation colonies. The second-generation colonies were then configured in 10-1... 8 A bacterial suspension of CFU / ml was prepared. Bone cement was made into small pieces with a diameter of 10 mm and a thickness of 1 mm. The samples were moistened with physiological saline, and excess saline was shaken off. The bone cement samples were then placed on MH culture plates coated with microorganisms and incubated in a constant temperature incubator at 37°C for 24 h. After removing the culture plates, optical photography was performed to observe whether a clear inhibition zone appeared around the bone cement samples. The diameter of the inhibition zone was measured using a measurement method.
[0043] Table 1
[0044] As can be seen from Table 1, the bone cement for orthopedic repair prepared in Examples 7-9 of this application has excellent mechanical properties, self-healing properties and antibacterial properties.
[0045] Comparative Examples 1 and 2 are comparative examples without the addition of modified toughening agents and antibacterial agents, respectively. The compressive strength, flexural strength, self-healing properties, and antibacterial properties of the bone cement prepared in Comparative Example 1 and Comparative Example 2 are significantly lower than those of the examples, further reflecting that the modified toughening agents and antibacterial agents prepared in this application can synergistically improve the mechanical properties, self-healing properties, and antibacterial properties of bone cement.
[0046] The compressive and flexural strengths of the bone cements prepared in Comparative Examples 3 and 4 were worse than those in the Example. This was mainly because the 5-oxopentanoic acid chain used in Comparative Example 3 was shorter than that of 12-oxododecanoic acid, resulting in decreased flexibility and increased rigidity of the modified toughening agent. The molecular chains could not dissipate energy through chain segment movement, leading to increased brittleness of the bone cement under external force. The p-hydroxyphenylethylamine used in Comparative Example 4 had only a single phenolic hydroxyl group and lacked a catechol group, resulting in poorer interfacial chemical anchoring between the modified toughening agent and the bone cement matrix, reduced stress transmission, and consequently, decreased compressive strength of the bone cement. Comparative Example 5 used a smaller number of Schiff bases in its modified toughening agent, resulting in lower compressive strength after failure.
[0047] The antibacterial properties of the bone cement prepared in Comparative Example 6 were lower than those in the Example. This was mainly because the antibacterial agent prepared using 4-aminobenzoyl chloride lacked a sulfonyl group. The rigid structure of the benzene ring and sulfonyl group caused the grafted gallic acid molecules to be perpendicular to the polydopamine surface, and the phenolic hydroxyl groups were fully exposed. This allowed the cement to exert a highly efficient antibacterial effect by disrupting the bacterial cell membrane and inhibiting enzyme activity. The lack of the sulfonyl group reduced the grafting rate of gallic acid and resulted in insufficient exposure, which in turn reduced the antibacterial properties of the bone cement.
[0048] The antibacterial properties of the bone cement prepared in Comparative Example 7 were lower than those in the Example. This was mainly because the p-hydroxybenzoic acid used to prepare the antibacterial agent lacked the poly-ortho-phenolic hydroxyl groups of gallic acid, which led to a sharp reduction in the number of active sites of the antibacterial group, loss of bacterial cell membrane destruction ability, and loss of enzyme inhibition function. Ultimately, it could not effectively kill bacteria, resulting in a significant reduction in the antibacterial properties of the bone cement.
[0049] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.
Claims
1. A bone cement for orthopedic repair, characterized in that, Includes solid powder and liquid components; The solid powder comprises the following components in parts by weight: 55-65 parts of composite calcium phosphate, 10-15 parts of bioactive glass, 2-3 parts of developer, 1-2 parts of hydroxyapatite, 8-12 parts of modified toughening agent, and 2-3 parts of nanocellulose fiber. The liquid phase component comprises the following components in parts by weight: 40-50 parts sodium alginate solution, 10-20 parts methacrylamide gelatin, 0.5-1 part transglutaminase, 30-60 parts citrate buffer, and 1-2 parts antibacterial agent.
2. The bone cement for orthopedic repair according to claim 1, characterized in that, The modified toughening agent is prepared by the following method: S1: Under nitrogen protection, pentaerythritol, 12-oxododecanoic acid and anhydrous toluene were mixed, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 4-dimethylaminopyridine were added. The mixture was reacted at 80-100℃ for 6-8 h to obtain intermediate 1. S2: Under nitrogen protection, intermediate 1, dopamine and anhydrous ethanol are mixed, triethylamine and ascorbic acid are added, and the mixture is reacted at 30-40℃ for 5-7 hours to obtain the modified toughening agent.
3. The bone cement for orthopedic repair according to claim 2, characterized in that, In step S1, the molar ratio of pentaerythritol to 12-oxododecanoic acid is 1:(4.1-4.3).
4. The bone cement for orthopedic repair according to claim 2, characterized in that, In step S2, the molar ratio of intermediate 1 to dopamine is 1:(4.05-4.2).
5. The bone cement for orthopedic repair according to claim 1, characterized in that, The antibacterial agent is prepared by the following method: N1: Under nitrogen protection, polydopamine and anhydrous DMF were mixed evenly, triethylamine was added and mixed evenly, and then 4-aminosulfonylbenzoyl chloride was added. The mixture was reacted at 30-40℃ for 5-7 hours to obtain intermediate A. N2: Under nitrogen protection, gallic acid and anhydrous DMF are mixed, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are added for activation; then the mixture is slowly added to the PBS buffer of intermediate A and reacted at 25-30℃ for 7-9 hours to obtain the antibacterial agent.
6. The bone cement for orthopedic repair according to claim 5, characterized in that, In step N1, the mass ratio of polydopamine to 4-aminosulfonylbenzoyl chloride is 1:(0.46-0.51).
7. The bone cement for orthopedic repair according to claim 5, characterized in that, In step N2, the mass ratio of intermediate A to gallic acid is 1:(0.25-0.27).
8. The bone cement for orthopedic repair according to claim 1, characterized in that, The composite calcium phosphate salt includes α-tricalcium phosphate and β-tricalcium phosphate, wherein α-tricalcium phosphate accounts for 70% by weight and β-tricalcium phosphate accounts for 30% by weight; the developer is tantalum powder; and the nanocellulose fiber is bacterial cellulose.
9. The bone cement for orthopedic repair according to claim 1, characterized in that, The sodium alginate solution has a concentration of 2 wt%; the citrate buffer solution has a concentration of 0.1 M and a pH of 6.
5.
10. A method for preparing bone cement for orthopedic repair according to any one of claims 1-9, characterized in that, Includes the following steps: (1) Weigh out the following by weight: 55-65 parts of compound calcium phosphate, 10-15 parts of bioactive glass, 2-3 parts of developer, 1-2 parts of hydroxyapatite, 8-12 parts of modified toughening agent, 2-3 parts of nanocellulose fiber, 40-50 parts of sodium alginate solution, 10-20 parts of methacrylamide gelatin, 0.5-1 part of transglutaminase, 30-60 parts of citrate buffer, and 1-2 parts of antibacterial agent; (2) First, freeze-dry the nanocellulose fibers to obtain dried nanocellulose fibers. Then, mix the composite calcium phosphate salt, bioactive glass, developer, hydroxyapatite, dried nanocellulose fibers and modified toughening agent in a three-dimensional mixer to obtain solid powder. (3) Mix methacrylamide gelatin with citrate buffer, stir and mix well in a 60°C water bath, and cool to room temperature in the dark; add transglutaminase and antibacterial agent to sodium alginate solution and disperse by sonication; Under light-protected conditions, the two solutions were mixed and stirred to obtain the liquid phase component; (4) Mix the solid powder and liquid components at a mass ratio of 3:1 and stir to obtain bone cement for orthopedic repair.
Citation Information
Patent Citations
High-bending-resistance injectable magnesium phosphate bone cement and preparation method thereof
CN120204462A
Solid-phase powder for bone cement composite material, bone cement composite material and application
CN114209878A
Absorbable suture line for surgical suture and preparation method thereof
CN120661721A
Minimally invasive treatment of vertebra (MITV) using calcium phosphate combination bone cement
JP2016209599A
Cement for bone surgery and method of its obtaining
RU2623211C1
Cited By
Injectable bone cement and preparation method thereof
CN121550482A
An injectable bone cement and a method for its preparation
CN121550482B
Injectable bone repair material containing bioactive glass and preparation method thereof
CN121944224A
Bioactive glass-based skull defect repair composite material and preparation method thereof
CN122182863A
Oral bone repair material based on bioactive glass and method for preparing the same
CN122440889A